The Need for Nigerian Journalists to Re-Define News Values - Garison, Anthony; Dangana, Yakubu Debora; Dapar, Jacob Plangnan (International Journal of Education, Management, and Technology, 2024)
Recent surveys show a decline in public interest in traditional news outlets like newspapers and television, possibly due to the constant exposure to negative stories that can lead to compassion fatigue. The major challenge is constituted by the adopted western news values which neglect our norms and focuses on praise singing the ruling elites. This article argues that, in order for Nigerian Journalists to effectively serve the nation's distinct socio-political context, traditional news ideals need to be redefined to fit our societal realities. Sensationalism and elitism are frequently given precedence over people-centered reporting in the current news values, which are primarily derived from Western media. Because of this misalignment, there is a gulf between the public and the media, which upholds social inequities and under-represents voices from marginalized groups. Nigerian Journalists should prioritize topics, stories and events that are important to their communities, support developmental or solution journalism, and hold authority figures accountable by reframing news principles. Adopting contextualized news values that represent Nigeria's political, cultural, and economic realities is necessary for this redefinition. The study suggests a framework for redefining news ideals that focus on social responsibility, local relevance, and people-centered reporting. Nigerian Journalists can recover their position as advocates for social change and catalysts for national advancement by implementing this approach. This would enhance development and audience engagement. Otherwise the public often diverts and avoids news when it makes them feel negative. And most of the western news values adopted relegate and places the masses in disadvantage disposition.